Prospective Evaluation of Bilateral Diaphragmatic Electromyograms During Cryoballoon Ablation of Atrial Fibrillation. (1st May 2015) - MIYAZAKI, SHINSUKE; HACHIYA, HITOSHI; TANIGUCHI, HIROSHI; NAKAMURA, HIROAKI; ICHIHARA, NOBORU; USUI, EISUKE; KUROI, AKIO; TAKAGI, TAKAMITSU; IWASAWA, JIN; HIRAO, KENZO; IESAKA, YOSHITO
Bilateral Diaphragmatic CMAPs During Cryoablation Background Left phrenic nerve injury (PNI) can occur during cryoballoon ablation of the left pulmonary veins (PVs). This study aimed to evaluate the feasibility of monitoring the bilateral phrenic nerve function during cryoballoon ablation of atrial fibrillation (AF). Methods Fifty consecutive paroxysmal AF patients undergoing cryoballoon ablation using one 28‐mm second‐generation balloon were prospectively enrolled. Bilateral diaphragmatic compound motor action potentials (CMAPs) were obtained from modified surface electrodes by pacing from the bilateral subclavian veins, and monitored during 3‐minute cryoballoon applications at the ipsilateral PVs. Results One hundred ninety of 202 PVs were successfully isolated exclusively using 28‐mm cryoballoons. CMAPs could be obtained in all except 3 cases with catheter inaccessibility in the left subclavian vein. The left and right CMAP amplitudes were similar at baseline (1.04 ± 0.41 mV vs. 1.01 ± 0.43 mV, P = 0.49). Among 105 left and 132 right PV applications while monitoring CMAPs, 2 (1.9%) and 13 (9.8%) applications were interrupted for a decreased CMAP amplitude (P = 0.01). Among them, CMAPs decreased due to right PNI in 4 applications/patients and to catheter dislodgement in the remaining applications. PNI remained in 1 and recovered in the remaining 3 patients one day after the procedure. Applications without requiring interruptions exhibited no significant CMAP amplitude changes throughout the applications, and the time‐course pattern was similar between the bilateral CMAPs (P = 0.292). Conclusions A stable bilateral diaphragmatic CMAP could be similarly obtained during cryoballoon applications in the vast majority of patients. Monitoring CMAPs might be useful to anticipate not only right but also left PNI during cryoballoon ablation.